Dampak Pandemi Covid-19 terhadap Kinerja Koperasi BMT Trans Mekar Sari Mandiri di Kecamatan Tanjung Lago Kabupaten Banyuasin - Sriati Sriati; Petty Elprina Br. Bukit; Sarah Poppy Siregar (Seminar Nasional Lahan Suboptimal, 2021)
Sriati S, Bukit EBB, Siregar PS. 2021. The impact of Covid-19 pandemic on cooperative performance of  Trans Mekar Sari Mandiri  BMT cooperative at Tanjung Lago District, Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 38-46.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Covid-19 pandemic has given impact on all aspects of life, including the social and economic aspects. This research aims to analyze the impact of the Covid-19 pandemic on the performance of cooperatives and the member participation. The research was conducted by survey method, on the performance of cooperatives at 2019 (before pandemic) and 2020 (during pandemic period), with 90 respondents from the BMT Trans Mekar Sari Mandiri cooperative. There are five measurement indicators for cooperative performance. The results showed that cooperative performance before the pandemic had high criteria score of 42.21 (94%), and during pandemic the score was 40.61 (90.2%). Member participation before the pandemic had moderate criteria score of 32.98 (73%) and during pandemic was on high criteria score 40.07 (89%). There are no significance  correlation between cooperative performance and member participation before pandemic (Rs = 0.17), but during pandemic the correlation was significant with  a = 0,01 (Rs = 0,476). It was concluded the impact of the Covid-19 pandemic on cooperative performance did not decrease criteria cooperative performance, but member participation was increased.